The effect and therapeutic compliance of adjuvant therapy in patients with cholangiocarcinoma after R0 resection: a retrospective study - Han Taek Jeong; Joonkee Lee; Hyeong Ho Jo; Ho Gak Kim; Jimin Han (Journal of Yeungnam Medical Science, 2023)
Background This study aimed to compare clinical outcomes between surveillance and adjuvant therapy (AT) groups after R0 resection for cholangiocarcinoma (CCA). Methods A total of 154 patients who underwent R0 resection for CCA at the Daegu Catholic University Medical Center between January 2010 and December 2019 were included. Overall survival (OS) and progression-free survival (PFS) were analyzed. Results The median follow-up duration was 899 days. There were 109 patients in the AT group and 45 patients in the surveillance group. The patients in the AT group were younger (67 years vs. 74 years, p<0.001) and included more males (64.2% vs. 46.7%, p=0.044). The proportion of patients with stage III CCA was larger in the AT group than in the surveillance group (13.8% vs. 2.2%, p=0.005). In addition, AT did not improve OS (5-year OS rate, 69.3% in the AT group vs. 64.2% in the surveillance group, p=0.806) or PFS (5-year PFS rate, 42.6% in the AT group vs. 48.9% in the surveillance group, p=0.113). In multivariate analysis using the Cox proportional hazards model, stage III CCA (hazard ratio [HR], 10.81; 95% confidence interval [CI], 2.92–40.00; p<0.001) was a significant predictor of OS. American Society of Anesthesiologists classification II (HR, 0.50; 95% CI, 0.31–0.81; p=0.005), and American Joint Committee on Cancer stages II (HR, 3.14; 95% CI, 1.25–7.89; p=0.015) and III (HR, 8.08; 95% CI, 2.80–23.32; p<0.001) were independent predictors of PFS. Conclusion AT after R0 resection for CCA did not improve OS or PFS.